Host CD73 impairs anti-tumor immunity - Salmi, Marko (Landes Bioscience, 2012)
The enzymatic activity of CD73 produces immune-suppressing adenosine. In CD73 deficient hosts, tumor growth and tumor infiltration by Tregs and type 2 immunosuppressive macrophages is reduced. Pharmacological inhibition of CD73 in wild-type mice has similar tumor-suppressing effects. Host CD73 on leukocytes and endothelial cells is thus detrimental for the anti-tumor immunity.